Sacred Grounds, Violent Histories: Unmaking and Remaking Baghdad’s Barāthā Mosque - Marashi, Taryn (Journal of Abbasid Studies, 2025)
A place of miracle and merit, the Barāthā mosque emerged as a key center for Shi’a scholarship and political activity in Abbasid Baghdad. However, medieval Sunni and Shi’i historians describe it as a site of intense conflict in the fourth/tenth and fifth/eleventh centuries. Ruling authorities and legal elites may have even destroyed this mosque more than once, viewing it as a nexus of theological deviation. Drawing on the perspectives of Sunni writers like Ibn al-Jawzī (d. 597/1201), this article examines what made the Barāthā mosque so especially controversial. By framing the mosque through the lens of aggression, it reveals how this place attracted, embodied, and fueled factional tensions in early medieval Baghdad.